(untitled) - Maxwell, David L. (xxiii, 561 p.)
This book provides comprehensive coverage of research methods as well as a foundation in statistical analysis vital for individuals in the communication sciences and disorders field. While most speech-language pathologists and audiologists pursue clinical practice rather than research careers, it is important to understand the scientific base that their clinical work is built upon
Keywords: Communicative disorders,Speech therapy,Chứng rối loạn giao tiếp,Ngôn ngữ trị liệu; Research,Methodology,Research,Methodology.,nghiên cứu,phương pháp luận,nghiên cứu,phương pháp luận